Kajian Peluang dan Tantangan Sosiologi Dakwah di Majelis Taklim Manbaul Irvani Walhikmah - Irvani, Fikri; Nurwahyu, Tb; Aziz, Fikri; Fahriani, Azira; Puspita, Fatima (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
Majelis taklim, As a non-formal Islamic educational institution, the Majelis Taklim (Islamic study group) plays a crucial role in fostering religious community, particularly in the modern era, marked by technological advancements, social dynamics, and changes in the community's lifestyle. This study aims to analyze the opportunities and challenges of Majelis Taklim in the modern era from a sociological perspective, using a case study of the Majelis Manbaul Irvani Walhikmah (Islamic study group) in Serang City. This research method uses a qualitative approach, collecting data through observation and interviews. The results indicate that Majelis Taklim has significant potential to expand the reach of Islamic preaching through digital media, improve the quality of technology-based learning, and strengthen religious social networks among its members. However, in this modern era, Majelis Taklim faces several challenges, including a lack of technological literacy among its members, competition with religious content on social media that is not always credible, and changes in the younger generation's interest in traditional religious activities. From a sociological perspective, Majelis Taklim maintains a strategic position as an agent of social transformation and guardian of religious values, but requires continuous innovation to adapt to the needs of modern society.